Obstacles to The Implementation of The Independent Curriculum in Schools (Case Study of MA/Mu'alimin Manba'ul Huda): Hambatan Penerapan Kurikulum Merdeka di Sekolah (Studi Kasus MA/Mu'alimin Manba'ul Huda) - Maula, Silma Fathatul; Ainunnisa, Maya; Rahman, Ahmad Syaeful (CV. Media Publikasi Profesional, 2024)
The implementation of the Independent Curriculum in Indonesia faces various challenges, especially in MA/Mu'alimin Manba'ul Huda, Bandung. The main obstacles include the lack of understanding of teachers regarding the concept and implementation of the Independent Curriculum as well as the inconsistency between the madrasah curriculum and the Independent Curriculum in the administrative aspect of assessment. The Independent Curriculum provides flexibility for schools to adjust learning, but this requires teachers to have higher managerial skills and creativity. To overcome this obstacle, several solutions have been proposed. First, more structured continuous training to improve teachers' understanding and skills. Second, the provision of comprehensive documentation related to the Independent Curriculum to facilitate adaptation. Third, mentoring by experienced teachers to encourage collaboration and knowledge sharing. In addition, the use of digital platforms is expected to accelerate the adaptation process by providing a space to share materials and experiences practically. Integrated assessment administration management between the two curricula is also the key to successful implementation. This requires a systematic system so that educational goals according to the Independent Curriculum can be achieved effectively. Through this approach, the existing challenges are expected to be overcome, so that the Independent Curriculum can encourage better quality education in Indonesia.